Inhibition and Reversal of Platelet Aggregation by Methyl Xanthines - Ardlie, G. N; Glew, G; Schultz, B. G; Schwartz, C. J (Thrombosis and Haemostasis, 1967)
The 3 methyl xanthines, caffeine, theobromine, and aminophylline inhibited and reversed platelet aggregation induced by ADP in vitro. Inhibition appeared to be noncompetitive and the effects of the methyl xanthines were not mediated through inhibition of platelet sulphydryl groups, chelation of calcium ions, or plasma pH change. A possible explanation for these properties has been suggested.